Conical antenna design for the excitation of RTL chamber for cell experiments. Issue 7 (26th April 2013) - Kim, Tae‐Hong; Lee, Hyeonjin
Abstract In this article, a conical antenna fed by coaxial line fed for the excitation of the radial transmission line (RTL) chamber is designed and fabricated. This antenna is analyzed by the finite‐difference time‐domain (FDTD) method and the input impedance is simulated. An RTL chamber was used by the device for in vitro experiments. The designed antenna has advantages, such as ultra‐broadband characteristic and omnidirectional radiation. The bandwidth of fabricated antenna has 630–2590 MHz at voltage standing wave ratio ≤ 2. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:1558–1560, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.27646